PENGARUH PENGGUNAAN SEARCH ENGINE, E-MAIL DAN MAILING LIST TERHADAP KUALITAS INFORMASI YANG DIHASILKAN DALAM LINGKUNGAN UNIVERSITAS BINA DARMA PALEMBANG - Andri - (Universitas Sriwijaya, 2009)
Internet is one of product or application as result from development of computer world, specially computer technology and telecommunication world. Internet as information technology which use computer technology. Computer is a tool which use to process an input and get result as output. To get a new information, human being needed to barter information with other people by internet. Simply, information technology needed to process with easy and accurate information. When we searching information by internet, we always using a software system which called as search engine. Search engine is a computer program which design to help people to find out files in computer. Beside that, there are email and mailing list. Email is an easy way to help people te accept and sending electronics mail with easy access, cheaper and fast time, only a second in time other people in other places will sent and get mail. This reaserch aims to know the effect of using search engine, email and mailing list toward information quality result at Bina Darma University. All data in this reaserch were collected using instrumentÂ in the form of questionnaire which has been distributed to 100 respondents. Those respondents were taken from six faculties which consist of Bina Darma lecture and students. Using SPSS 12.0 all data is analyzed. The result of this reaserch is that there are positive and significant influences among 3 variables search engine, email and mailing list toward information quality result at Bina Darma University both partially or simultaneously. Â Keywords : Internet, search engine, email and mailing list